1996
DOI: 10.1006/dbio.1996.0042
|View full text |Cite
|
Sign up to set email alerts
|

Strong Induction of Activin Expression after Injury Suggests an Important Role of Activin in Wound Repair

Abstract: Activins are members of the transforming growth factor beta (TGF beta) superfamily, which comprises a growing group of dimeric proteins. TGF beta and several other members of this superfamily are known to play an important role in wound healing. However, expression of activin during wound healing has not been demonstrated so far. In this study we have analyzed the expression pattern of activin and activin receptors in normal and wounded skin. We found a large induction of activin A and a minor induction of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
161
1
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 181 publications
(173 citation statements)
references
References 5 publications
8
161
1
3
Order By: Relevance
“…D Rotzer et al the hyperproliferative wound epidermis (Hu¨bner et al, 1996, and this study), and indicates that endogenous activin also regulates the levels of Id proteins. Thus, in addition to TGF-b (Ling et al, 2002;Kretschmer et al, 2003;Siegel et al, 2003;Kowanetz et al, 2004), activin was identified as a novel regulator of Id gene expression.…”
Section: Id Proteins In Epidermal Homeostasissupporting
confidence: 69%
See 4 more Smart Citations
“…D Rotzer et al the hyperproliferative wound epidermis (Hu¨bner et al, 1996, and this study), and indicates that endogenous activin also regulates the levels of Id proteins. Thus, in addition to TGF-b (Ling et al, 2002;Kretschmer et al, 2003;Siegel et al, 2003;Kowanetz et al, 2004), activin was identified as a novel regulator of Id gene expression.…”
Section: Id Proteins In Epidermal Homeostasissupporting
confidence: 69%
“…For this purpose, we analysed the expression of these transcriptional regulators during the healing process of full-thickness excisional mouse wounds (Figures 2 and 3), since activin is highly expressed between day 1 and day 7 of wound repair (Hu¨bner et al, 1996). The time points that we chose for the expression analysis are characteristic for the three different phases of repair.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations